EVALUATION OF IN VITRO ANTIOXIDANT ACTIVITY AND ESTIMATION OF TOTAL PHENOL AND FLAVONOID CONTENT OF ETHANOLIC LEAF EXTRACT OF IRIS KASHMIRIANA - Khalid, Shah; Alia, Aparna; Pn, Shrivastava; Rather, Muzafar Akbar; Sheikh, Muzafar Ah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The main aim of this study was to determine the in vitro antioxidant activity of Iris kashmiriana ethanolic leaf extract and also total phenol and flavonoid content was evaluated. Methods: Total phenol content (TPC) was determined by Folin–Ciocalteu method, total flavonoid content (TFC) was estimated by aluminum trichloride spectrophotometer method. Furthermore, antioxidant activity was revealed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, hydrogen peroxide (H2O2) scavenging activity, and reducing power assay. Results: The ethanolic leaf extract of I. kashmiriana showed TPC of 13.25±0.57 μg/100 μg gallic acid equivalents and TFC of 33.61±3.37 μg/100 μg rutin equivalents. The DPPH assay revealed IC50 of 0.418 mg/ml and for H2O2 radical scavenging IC50 was 0.476 mg/ml for the plant extract while as reducing power assay revealed concentration-dependent absorption values which clearly determine the antioxidant property of plant. Conclusion: From the results, it is apparent that I. kashmiriana ethanolic leaf extract possessed potential antioxidant activity which can be used to cure wide range of diseases.